Mental health and Covid-19: tafakur as self care technique during pandemic - Nur Yani, Che Hussin; Muhammad Nubli, Abdul Wahab; Norizan, Yusof (Kolej Universiti Islam Pahang Sultan Ahmad Shah (KIPSAS), 2022)
The COVID-19 pandemic has impacted people all around the world in a variety of ways. Due to many factors such as death, unemployment, quarantine, and more, this pandemic contributes to a rise in mental pressure and anxiety throughout society. Tafakur technique is a psychospiritual approach that can help people regulate their emotions and relax. It is also a sort of ibadah that helps people feel connected to Allah. Human senses are the primary gateway to receiving numerous stimuli from the environment. Several empirical studies have been conducted to explain the positive benefits on mental health that can be attained when a person connects with nature. He may profit in terms of psychology, benefits to nature, and performing ibadah to Allah if he has such link mixed with tafakur.